A critical analysis of the relationship between the South African Defence Force and the South African media from 1975-83 - Kirsten, Frederik Fouche (Rhodes University, Faculty of Humanities, Department of History, 2016)
The main focus of this thesis is to show the nature of the relationship between the South African Defence Force and the local media from 1975-83. The thesis will analyse issues specifically relating to the nature of the relationship and show how and why they are relevant to understanding the authoritarianism of the apartheid state. The nature of the relationship will be conceptualised by way of the analogy of a marriage. The thesis will show that for the SADF the relationship was "a marriage of convenience" whereas for the media it was a "marriage of necessity" . This relationship operated within the context of a highly militarised society that has been termed a "Garrison State" . The apartheid government introduced legislation governing reporting of defence matters and the media (namely the South African Defence Act 1957 including amendments made up until 1980) that imposed legal constraints within which defence correspondents had to operate. Moreover, the MID's secret monitoring of the local media reveals the extent to which the military distrusted the media. A sampling of the coverage of defence matters in a selection of newspapers will reveal how their editorial staffs and reporters operated in a situation where the flow of information was controlled by the military. This will also show that certain defence correspondents cultivated close relations with SADF personnel to ensure that they were kept informed. The thesis will also show how the SADF reacted to the international media exposure of Operation Savannah and Operation Reindeer and how the SADF sought to limit the damage to its reputation by clamping down on the local media. The creation of two media commissions both headed by Justice MT Steyn, set out to investigate the manner in which local media reported on security issues in an environment in which the media and the public were confronted by the "Total Strategy" discourse of the apartheid government. The working relationship between the SADF and the media encapsulated in the thesis can be described as highly complex and the use of the "marriage" analogy assists in understanding this relationship.
Keywords: South Africa -- South African Defence Force; Mass media -- Political aspects -- South Africa; Freedom of information -- South Africa